IMPACT OF THREE DIFFERENT DOUBLE BAFFLE DESIGNS ON THE THERMAL PERFORMANCE OF SQUARE DUCTS - Withada Jedsadaratanachai; Amnart Boonloi (My University, 2022)
A premiere free-access and peer-reviewed frontier journal site, serving the needs of the thermal-fluids community. See the latest research or submit an article. Quickly share your research with the global thermal-fluids community, for increased citations and impact at no cost.
Keywords: Baffle; Thermal fluids; Square (algebra); Frontier; Heat Transfer and Optimization